Elements of environmental management systems according to iso 14001 relevant from the point of view of an insurance company – the results of empirical research - Lemkowska, Malwina; Wiśniewska, Dorota (Publishing House of Wroclaw University of Economics and Business, 2021)
The following paper presents the findings of the research concerning environmental insurance and environmental management systems in conformity with ISO 14001, and is a part of a broader research project. It shows the interrelation between the attributes of organisations managed according to ISO 14001 and the implementation therein of RSS (relevant systemic solutions). RSS refer to elements of environmental management systems (EMS) relevant from the point of view of an insurance company which provides environmental insurance. The RSS were divided into four groups of dependent variables (personal integration variables, project variables, informative potential variables and volume of risk variables). The attributes of the organisations managed according to ISO 14001 were catalogued in three sets of independent variables (systemic, organisational and awareness-related features). The research comprised statistical analysis in order to identify the interrelations between the above variables. The analysis has shown that the largest number of correlations was obtained in the area of the informative potential variables and selected scope of volume of risk variables (especially these referring to monitoring of the aspects affecting the volume of insurance risk, taking preventive and repressive actions and planning the response procedures to potential emergency situations). Simultaneously, statistically significant relations were most frequently identified between the above RSS and the awareness-related attributes of organisations. The higher in the respondents’ opinion was the likelihood of the damage occurrence, the likelihood and severity of its particular consequences, as well as the impact of both the legal acts and particular regulation categories in environmental area, the more frequently they implemented the systemic solutions essential to provision of insurance cover.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 271-306
Keywords: environmental insurance; environmental management system ISO 14001; RSS; EMS